Using interpersonal process recall to understand empowerment processes in a collaborative care intervention for people with a diagnosis of psychosis. Issue 4 (2nd October 2019) - Baker, Elina; Gwernan-Jones, Ruth; Britten, Nicky; McCabe, Cathy; Gill, Laura; Byng, Richard; Gask, Linda
ABSTRACT: Evaluation of recovery-focused interventions for people with psychosis may be enhanced by the use of Interpersonal Process Recall (IPR). The aim of this study was to examine whether the inclusion of IPR alongside semi-structured interviews in the formative evaluation of a novel collaborative care intervention increased understanding about both practitioner and service user experiences. It also explored the impact of the IPR process on participants. Four service users and the practitioner delivering the intervention participated in semi-structured interviews and an adapted IPR process. The themes identified from different data sources were systematically compared using framework analysis. Semi-structured interviews indicated that the intervention was operating as intended but IPR data revealed exceptions. Practitioner IPR interviews identified practitioner barriers to delivery and fostered critical self-reflection. Service user IPR interviews facilitated critical feedback but also caused some distress. Interviews gave more information about organisational level contextual factors. IPR increased understanding of how the intervention was being delivered and experienced. IPR should be used alongside other forms of qualitative data collection. The potential of IPR to impact on intervention delivery should be taken into account. Further research is needed to establish for whom IPR is likely to be most effective.